Structural basis of antifolate recognition and transport by PCFT - Parker, JL; Deme, JC; Kuteyi, G; Wu, Z; Huo, J; Goldman, ID; Owens, RJ; Biggin, PC; Lea, SM; Newstead, S (Springer Nature, 2021)
Folates (also known as vitamin B9) have a critical role in cellular metabolism as the starting point in the synthesis of nucleic acids, amino acids and the universal methylating agent S-adenylsmethionine1,2. Folate deficiency is associated with a number of developmental, immune and neurological disorders3,4,5. Mammals cannot synthesize folates de novo; several systems have therefore evolved to take up folates from the diet and distribute them within the body3,6. The proton-coupled folate transporter (PCFT) (also known as SLC46A1) mediates folate uptake across the intestinal brush border membrane and the choroid plexus4,7, and is an important route for the delivery of antifolate drugs in cancer chemotherapy8,9,10. How PCFT recognizes folates or antifolate agents is currently unclear. Here we present cryo-electron microscopy structures of PCFT in a substrate-free state and in complex with a new-generation antifolate drug (pemetrexed). Our results provide a structural basis for understanding antifolate recognition and provide insights into the pH-regulated mechanism of folate transport mediated by PCFT.